Islamic Virtue Ethics and Career Adaptability: Redesigning Islamic Education Students’ Character for the Modern Workforce - Sendi, Okni Aisa Mutiara; Pransiska, Selvi (El-Rusyd, 2026)
This study aims to explore how Islamic virtue ethics is interpreted as the foundation for redesigning the character of Islamic Education students in facing the transition from academic life to the modern world of work. This study employed an interpretive qualitative approach with a case study design. Data were collected through semi-structured interviews, focus group discussions, written reflections, and field notes involving Islamic Education students who were in the career preparation phase. The data were analyzed using reflexive thematic analysis to identify patterns of meaning related to Islamic values, character, career adaptability, and professional dilemmas. The findings show that amanah shapes professional responsibility, honesty, discipline, and workplace trust. Sabr and tawakkul build spiritual-professional career resilience in facing anxiety, failure, job rejection, and future uncertainty. Ihsan and ikhlas form a meaningful work orientation that emphasizes quality, social benefit, service, and worship value. This study also found that Islamic Education students negotiate Islamic values with the pragmatic demands of the workplace; therefore, career adaptability is not understood as unlimited flexibility, but as ethical adaptation. This article offers the concept of virtue-based career adaptability as a theoretical contribution to character education in Islamic Education. The implications of this study emphasize the need for Islamic virtue-based career guidance, the integration of character and employability, and the development of value-based career maps for Islamic Education students in a contextual, sustainable, and ethically grounded manner in the complex modern world of work.